Yamaguchi esterification: a key step toward the synthesis of natural products and their analogs—a review - Munir, Ramsha; Zahoor, Ameer Fawad; Anjum, Muhammad Naveed; Mansha, Asim; Irfan, Ali; Chaudhry, Aijaz Rasool; Irfan, Ahmad; Kotwica-Mojzych, Katarzyna; Glowacka, Mariola; Mojzych, Mariusz (Frontiers in Chemistry, 2024)
The Yamaguchi reagent, based on 2,4,6-trichlorobenzoyl chloride (TCBC) and 4-dimethylaminopyridine (DMAP), is an efficient tool for conducting the intermolecular (esterification) reaction between an acid and an alcohol in the presence of a suitable base (Et3N or iPr2NEt) and solvent (THF, DCM, or toluene). The Yamaguchi protocol is renowned for its ability to efficiently produce a diverse array of functionalized esters, promoting high yields, regioselectivity, and easy handling under mild conditions with short reaction times. Here, the recent utilization of the Yamaguchi reagent was reviewed in the synthesis of various natural products such as macrolides, terpenoids, polyketides, peptides, and metabolites.